Proteomics profiling of serum exosomes from azithromycin-sensitive and resistant Mycoplasma pneumoniae-infected patients reveals candidate biomarkers for diagnosis - Fan, Huifeng; Huang, Feng; Chen, Chen; Ren, Qiaoli; Zhou, Jing; Yang, Diyuan; Lu, Gen (Frontiers in Medicine, 2025)
IntroductionMycoplasma pneumoniae (M. pneumoniae) infections are prevalent among school-age children, and an increasing number of patients are developing resistance to azithromycin (AZM). However, effective biomarkers for diagnosing AZM resistance are currently lacking. This study aimed to identify potential biomarkers for AZM resistance in M. pneumoniae infections by analyzing serum exosomes.MethodsSerum samples were collected from M. pneumoniae-infected patients before and after AZM treatment and were categorized into two groups: responders and non-responders. Serum exosomes were isolated and analyzed using nanoparticle tracking analysis (NTA) and proteomics profiling by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Differential protein expression patterns were compared between AZM-sensitive and resistant patients, and potential biomarkers were identified and validated.ResultsDistinct exosomal protein expression patterns were observed between AZM-sensitive and resistant patients. The HIF-1 and IL-17 signaling pathways were found to be associated with AZM resistance. Four proteins (KCTD12, LTF, TF, and MPO) were identified as potential biomarkers for distinguishing responders from non-responders. These biomarkers demonstrated over 80% sensitivity and 73.33% specificity in differentiating between the two groups.ConclusionThe study successfully identified four potential biomarkers (KCTD12, LTF, TF, and MPO) for AZM resistance in M. pneumoniae infections. These biomarkers may serve as useful diagnostic tools in clinical settings, aiding in the identification of patients who may not respond to AZM treatment. Future research should focus on validating these biomarkers in larger cohorts and exploring their potential applications in clinical practice.